Mistake or Manipulation? Conceptualizing Perceived Mis- and Disinformation among News Consumers in 10 European Countries. (October 2022) - Hameleers, Michael; Brosius, Anna; Marquart, Franziska; Goldberg, Andreas C.; van Elsas, Erika; de Vreese, Claes H.
In the midst of heated debates surrounding the veracity and honesty of communication, scholarly attention has turned to the conceptualization of mis- and disinformation on the supply-side of (political) communication. Yet, we lack systematic research on the conceptualization of perceived mis- and disinformation on the demand-side. Original survey data collected in ten European countries ( N  = 6, 643) shows that news consumers distinguish general misinformation from disinformation. Yet, the high correlation between the two dimensions indicates that disinformation perceptions may be regarded as a sub-type of misinformation perceptions in which intentional deception is a core element. This paper aims to make a contribution to the misinformation and media credibility literature by proposing a first conceptualization of perceived untruthfulness corresponding to increasing levels of cynicism and skepticism toward the factual status and honesty of information.